Quark-Nova Explosion inside a Collapsar: Application to Gamma Ray Bursts - Rachid Ouyed; Denis Leahy; Jan Staff; Brian Niebergal (Advances in Astronomy)
If a quark-nova occurs inside a collapsar, the interaction between the quark-nova ejecta (relativistic iron-rich chunks) and the collapsar envelope leads to features indicative of those observed in Gamma Ray Bursts. The quark-nova ejecta collides with the stellar envelope creating an outward moving cap (Γ∼ 1–10) above the polar funnel. Prompt gamma-ray burst emission from internal shocks in relativistic jets (following accretion onto the quark star) becomes visible after the cap becomes optically thin. Model features include (i) precursor activity (optical, X-ray, γ-ray), (ii) prompt γ-ray emission, and (iii) afterglow emission. We discuss SN-less long duration GRBs, short hard GRBs (including association and nonassociation with star forming regions), dark GRBs, the energetic X-ray flares detected in Swift GRBs, and the near-simultaneous optical and γ-ray prompt emission observed in GRBs in the context of our model.